2016
DOI: 10.1093/mnras/stw3070
|View full text |Cite
|
Sign up to set email alerts
|

The precise and powerful chaos of the 5:2 mean motion resonance with Jupiter

Abstract: This work reexamines the dynamics of the 5:2 mean motion resonance with Jupiter located in the Outer Belt at a ∼ 2.82 AU. First, we compute dynamical maps revealing the precise structure of chaos inside the resonance. Being interested to verify the chaotic structures as sources of natural transportation routes, we additionally integrate 1000 massless particles initially placed along them and follow their orbital histories up to 5 Myr. As many as 99.5% of our test particles became Near-Earth Objects, 23.4% migr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(50 citation statements)
references
References 34 publications
6
42
2
Order By: Relevance
“…Phaethon is the parent body of the Geminids, one of the most predominant meteor streams. Several studies (de Leon et al 2010;Todorovic 2017Todorovic , 2018 show that Phaethon is likely originating from the family of asteroids associated with (2) Pallas, one of the largest members of the Main Belt. Pallas is clearly hydrated (Usui et al 2019 and references therein) while Phaethon is not (Kareta et al 2018).…”
Section: Discussion a N D I M P L I C At I O N Smentioning
confidence: 99%
“…Phaethon is the parent body of the Geminids, one of the most predominant meteor streams. Several studies (de Leon et al 2010;Todorovic 2017Todorovic , 2018 show that Phaethon is likely originating from the family of asteroids associated with (2) Pallas, one of the largest members of the Main Belt. Pallas is clearly hydrated (Usui et al 2019 and references therein) while Phaethon is not (Kareta et al 2018).…”
Section: Discussion a N D I M P L I C At I O N Smentioning
confidence: 99%
“…In the work of de Leon et al (2010), where both 5:2 and 8:3 MMRs where studied the probability for this connection was 2 per cent, and in Bottke et al (2002) for example, this probability was zero. In Todorović (2017) we applied the same methodology as done here and found that 8 per cent of test objects placed into the 5:2 MMR reached the orbit of Phaethon; much less than in this work, because, in Todorović (2017), the resonance was mapped in the lower inclined orbital plane of Ceres (at i = 10 deg). Choosing particles at the most unstable parts of the two resonances, but in the orbital plane of Pallas increased the Pallas-Phaethon transportation efficiency multiply times.…”
Section: Resultsmentioning
confidence: 81%
“…It is important that the calculation times of the maps are short, because in this way the fine structure of chaos in the resonance can be clearly detected (Guzzo and Lega 2014;Todorović 2017). The more unstable parts, easily noticeable on the maps, represent 'good' starting positions for diffusion.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…As a result, the FLI increases almost linearly with time for chaotic orbits and approximately logarithmically for regular orbits. Therefore, the computation of FLI on a grid of initial conditions x(0) for the same fixed initial deviation vector allows us to map the chaos in a dynamical system (FLI map) (Lega et al 2016;Todorović 2017).…”
Section: Methods -Flimentioning
confidence: 99%